The therapist's notebook for systemic teletherapy : creative interventions for effective online therapy - Cobb, Rebecca A. (New York, NY : Routledge, 2024)
"Many therapeutic activities that engage clients in in-person therapy rooms are not obviously available via telehealth. Yet, there are creative, practical, and easy ways to intervene in teletherapy that go beyond talk therapy. The Therapist's Notebook for Systemic Teletherapy: Creative Interventions for Effective Online Therapy provides systemic teletherapy activities and interventions for a variety of topics and presenting problems. Forty chapters are arranged into seven parts: setup and preparation, self of the therapist, children and adolescents, adults, intimate relationships, families, and training and supervision. Leading experts provide step-by-step guidelines on setup, instructions, processing, and suggestions for follow-up for interventions that are grounded within foundational therapy theories/models and evidence-based practice. This book explores both new intervention strategies and ways to adapt in-person therapy interventions for telehealth. This book provides creative inspiration and practical advice for novice and experienced family therapists, clinical social workers, counselors, play therapists, psychologists, psychiatrists, and others in related fields"--
Keywords: Internet in psychotherapy; PSYCHOLOGY / Psychotherapy / Couples & Family; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Psychotherapy / Group